2018
DOI: 10.1108/rpj-05-2016-0070
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment of electron beam melted (EBM) Ti-6Al-4V: microstructure to mechanical property correlations

Abstract: Purpose The paper presents a wide range of post processing heat treatment cycles performed to Electron Beam Melted (EBM) Ti6Al4V alloy and establishes correlations of heat treat process to microstructure and mechanical property (microhardness). The research also identifies the optimal heat treatment to obtain the best microstructure and mechanical properties (hardness and tensile). Design/methodology/approach Rectangular bars fabricated using EBM was used to study the different heat treatment cycles. A varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…The microstructures show differences between the top and side faces due to the variations in thermal gradients that existed along these faces. Overall, the as-printed EBM samples exhibited superior strength compared to those of the wrought [32] and heat-treated samples [54] due to the refined lamellar α and β microstructure.…”
Section: Electron Beam Melting Of Ti6al4vmentioning
confidence: 96%
“…The microstructures show differences between the top and side faces due to the variations in thermal gradients that existed along these faces. Overall, the as-printed EBM samples exhibited superior strength compared to those of the wrought [32] and heat-treated samples [54] due to the refined lamellar α and β microstructure.…”
Section: Electron Beam Melting Of Ti6al4vmentioning
confidence: 96%
“…In general, the microstructure of EBM Ti-6Al-4V alloys is diversified and the mechanical properties vary greatly. Fine needle-like α phase separated by the β phase was found to exist in EBM Ti-6Al-4V parts [5][6][7][8], while fine lamellar α/β dual-phase microstructure was a typical microstructure of EBM parts [4,9,10]. Sinan et al [8] found martensite in the top area of the samples with heights of 2 and 5 mm, but the martensite in the top area of the samples with a height of 18 mm was not obvious.…”
Section: Introductionmentioning
confidence: 95%
“…Hrabe et al [20] demonstrated that vertically oriented EBM Ti-6Al-4V parts showed a 30% lower elongation compared to horizontally oriented parts. Different heat treatments were performed on Ti-6Al-4V by Galarraga et al [22] and Raghavan et al [5] to study the effects of heat treatments on the unique microstructure formed during the EBM fabrication process. When different heat treatment cycles are applied to EBM Ti-6Al-4V materials, the final microstructure can be tailored, and the mechanical properties can also be improved.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Figure 23c, it can be seen that layer-2 receives several heat cycles due to electron beam scans on subsequent layers as compared to layer-8, which only receives 2 heat cycles (see Figure 23d). Usually, the higher heat accumulation and rapid extraction of heat favor the higher concentration of the beta phase and vice versa for the alpha phase [35,36]. Therefore, in Figure 23a, more β phase and wider α grains could be observed.…”
Section: Microstructure Evolutionmentioning
confidence: 97%